Biomechanical Analysis of Various Knee Prosthesis Biomaterials Under Different Flexion Angles Using Finite Element Method - S.J, Sanjay.; C, Shashishekar. (Journal of Neonatal Surgery, 2025)
This study employs finite element analysis (FEA) to investigate the biomechanical performance of various biomaterials commonly used in total knee arthroplasty (TKA) under different geometric and flexion conditions. Three-dimensional CAD models of knee implants were developed with varying femoral component geometries—diameters of 60 mm, 65 mm, 70 mm, 75 mm, and 80 mm; sagittal radii of 45 mm and 50 mm, all analysed at a fixed flexion angle of 30°. The materials evaluated include Ti-6Al-4V, Co-Cr-Mo, and stainless steel for the femoral component, and ultra-high molecular weight polyethylene (UHMWPE) for the tibial insert. Realistic material properties and simulated physiological loading were applied to assess the implant's mechanical response. Parameters such as Von Mises stress, The findings provide critical insight into the effect of material selection and femoral geometry on stress distribution and overall implant durability. This analysis aids in optimizing TKA design for improved performance, longevity, and patient outcomes..